When Noise Fails to Disrupt Working Memory: An Experimental Study on Smartphone-Addicted Users - Afifah, Salma Ayu; Nasution, Dhia Adlan; Maharani, Aprilia Rizki; Srisayekti, Wilis; Rubiyanti, Yanti; Rini, Yulia Eka; Zakaria, Suwaibah (Faculty of Psychology, Universitas Gadjah Mada, 2025)
This study aimed to examine the causal impact of the irrelevant sound effect (ISE)—specifically background speech noise—on the working memory performance of university students with smartphone addiction. Working memory, a cognitive system that supports the simultaneous storage and processing of information, plays a crucial role in academic tasks that require sustained concentration. The study employed a quantitative experimental method with a between-subjects design, comparing two groups: one exposed to background speech noise and a control group without auditory interference. Working memory performance was measured using the automated operation span (O-Span) task, which requires participants to solve mathematical equations while remembering sequences of letters. A total of 66 university students who scored high on the Smartphone Addiction Scale participated in the study. Statistical analyses revealed no significant differences between the two groups in either processing or storage performance. These findings suggest that exposure to background speech noise does not necessarily impair working memory, at least among individuals with high levels of smartphone use. One possible explanation is that these individuals may have developed cognitive adaptations that allow them to filter out distracting sounds—an ability potentially shaped by habitual digital multitasking. This study contributes to the growing evidence that the impact of the ISE is not universal and may be moderated by the unique characteristics of specific populations.